2011
DOI: 10.1080/02701367.2011.10599784
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Physical Education on Physical Activity Levels of Urban Elementary Students

Abstract: The purpose of this study was to examine the role of physical education in shaping physical activity patterns. Seventy-one Hispanic and African American elementary students participated in the study. Students attended one 30- and one 60-min physical education class weekly. Pedometer steps were used to estimate physical activity. Data suggest that students did not engage in enough physical activity on a daily basis to incur health benefits. There were significant step differences in 0-, 30-, and 60-min physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
6

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 36 publications
4
23
0
6
Order By: Relevance
“…[32][33][34] In addition, children encouraged to be physically active in school have been shown to be more active outside of school compared with children whose school-day PA was restricted, and other studies have shown children to be more active during the school week compared with weekend days. [35][36][37] These findings, in concert with the weak correlation between parent-child PA levels, corroborate the importance of school-day PA.…”
Section: Discussionsupporting
confidence: 70%
“…[32][33][34] In addition, children encouraged to be physically active in school have been shown to be more active outside of school compared with children whose school-day PA was restricted, and other studies have shown children to be more active during the school week compared with weekend days. [35][36][37] These findings, in concert with the weak correlation between parent-child PA levels, corroborate the importance of school-day PA.…”
Section: Discussionsupporting
confidence: 70%
“…21 Similarly, PE was shown to be the single greatest contributor (23%–25%) to in-school steps in American Indian children 22 and Hispanic and non-Hispanic girls in the Southwest. 23 Importantly, both boys and girls experienced benefits of PE, which supports previous research.…”
Section: Discussionmentioning
confidence: 94%
“…Only 2 other very recent studies have reported directly on the association between PE and total SED time, whereby 1 group reported an association between increased PE participation and reduced school-time and overall daily SED (Sigmund et al 2014), while others reported similar SED time on PE and non-PE days (Chen et al 2014). A number of prior studies have shown benefits of PE in terms of higher overall MVPA levels in children (Chen et al 2014;Lonsdale et al 2013;Pate et al 2007;Sallis et al 1997;Sigmund et al 2014), PE accounting for about 16%-17% of total daily PA (Cawley et al 2007;Dauenhauer and Keating 2011;Meyer et al 2013), and children not compensating with increased after-school PA on days of restricted in-school PA (Dale et al 2000). This finding is not universal, however, as some have reported no association between PE and total daily PA, suggesting that children may in fact compensate on non-PE days (Mallam et al 2003;Wilkin et al 2006).…”
Section: Pementioning
confidence: 95%